Analisis Pengaruh Modal, Tingkat Upah, dan Nilai Output Terhadap Penyerapan Tenaga Kerja Industri di Pulau Jawa - Gabriella Maylani Prasetyaningrum; Adhita Dwi Kirana; Salmadella Regita Puri (STIKes Ibnu Sina Ajibarang, 2025)
This study attempts to examine the influence of three economic factors, namely capital, wage rate, and output value in the context of labor absorption in the industrial sector operating in Java. The study uses a quantitative approach method by utilizing secondary data sourced from BPS during the period 2018-2023, where panel data regression analysis with the Fixed Effect Model (FEM) approach is applied to test the relationship between variables. The results of the analysis indicate that the capital factor does not have a significant impact on the labor absorption process. Meanwhile, the wage level shows a correlation in the same direction as labor absorption, this influence is not proven to be significant when tested statistically. On the other hand, the output value shows a significant positive influence on labor absorption. These findings reveal how complex the interactions between economic factors are in the Java region, which have important implications for the development of employment policies and inclusive development strategies. A comprehensive approach is needed to support the sustainability of industrial growth and improve the quality of human resources in the future.